2020
DOI: 10.3390/biomedicines8110473
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz-Type Peptides from the Sea Anemone Heteractis crispa Demonstrate Potassium Channel Blocking and Anti-Inflammatory Activities

Abstract: The Kunitz/BPTI peptide family includes unique representatives demonstrating various biological activities. Electrophysiological screening of peptides HCRG1 and HCRG2 from the sea anemone Heteractis crispa on six Kv1.x channel isoforms and insect Shaker IR channel expressed in Xenopus laevis oocytes revealed their potassium channels blocking activity. HCRG1 and HCRG2 appear to be the first Kunitz-type peptides from sea anemones blocking Kv1.3 with IC50 of 40.7 and 29.7 nM, respectively. In addition, peptides m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Sea anemone Kunitz-type peptides can block Kv channels [ 60 ], which are known to be actively involved in the regulation of neuronal processes and considered as potential therapeutic targets for Parkinson’s disease [ 61 , 62 ]. Earlier we reported that HCRG1 and HCRG2 block several Kv1.x isoforms (Kv1.1, Kv1.2, Kv1.3, Kv1.6) in nM range [ 31 ], and now they showed full suppression of ROS formation in 6-OHDA-treated cells, but these peptides did not affect cell viability. They probably will be active in vivo similar to Kunitz-type toxin PcKuz3 of P. caribaeorum showing neuroprotective activity on 6-OHDA treated zebrafish Danio rerio [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea anemone Kunitz-type peptides can block Kv channels [ 60 ], which are known to be actively involved in the regulation of neuronal processes and considered as potential therapeutic targets for Parkinson’s disease [ 61 , 62 ]. Earlier we reported that HCRG1 and HCRG2 block several Kv1.x isoforms (Kv1.1, Kv1.2, Kv1.3, Kv1.6) in nM range [ 31 ], and now they showed full suppression of ROS formation in 6-OHDA-treated cells, but these peptides did not affect cell viability. They probably will be active in vivo similar to Kunitz-type toxin PcKuz3 of P. caribaeorum showing neuroprotective activity on 6-OHDA treated zebrafish Danio rerio [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for some of them, cellular targets have already been found that allow explaining their biological effects. It has been found that TRPV1 is the target of APHC1-3 (partial inhibition up to 50%) and HCRG21 (full inhibition) resulting in analgesic and anti-inflammatory effect in mice [ 10 , 12 , 29 , 30 ], whereas Kv channels are the targets of HCRG1 and HCRG2 that block them and demonstrate anti-inflammatory activity reducing expression level of TNF-α, IL-6, and proIL-1β in macrophages [ 14 ], as well as suppressing TNF-α production in acute carrageenan-induced edema model [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrate that, by simply introducing one additional residue, the toxin is converted from a Na V 1.7 activator into an inhibitor, which can be crucial for designing effective analgesic leads. Novel toxins with potential anti-inflammatory activity are further reported from the venom of a sea anemone [ 68 ]. In addition to their proposed medical applications, venom components are also useful tools for research.…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…The HCRG21 fold correctness was assessed using NMR spectroscopy on a Bruker Avance III 700 MHz spectrometer (Bruker Biospin, San Jose, CA, USA) equipped with a triple resonance z-gradient TXO probe, as described previously [16].…”
Section: Production Of Recombinant Peptidementioning
confidence: 99%
“…This procedure was conducted as we described in a previous article [16]. The animals were terminally anaesthetized with sodium pentobarbital (40 mg per mouse i.p., Euthatal, Merial Animal Health, Essex, UK) 24 h after carrageenan injection.…”
Section: Animals Euthanasia Procedures and Blood Samplingmentioning
confidence: 99%